PENGARUH KEGIATAN BACA TULIS AL-QUR’AN (BTQ) TERHADAP SIKAP RELIGIUS MAHASISWA IKIP SILIWANGI - Dini Anggraeni; Rita Rohimatul Barokah; Sary Sukawati (IKIP Siliwangi, 2019)
This study is the result of analysis to see the influence of reading and writing about the religious attitude of the students. Subject of the study is a student of IKIP Siliwangi. The data used for the analysis is a questionnaire with guttman scale. Data are analyzed based on instruments that focus on the success and influence of literacy activities of the Quran. The method used is the developmental experimental method with the analysis of quantitative-qualitative approach. From the guttman scale analysis, the point of influence is in the 50% -100% range ie the BTQ program 84.8% and its impact on religious attitudes 89.6%. So that can be said The Influence of Reading Program Al-Quran on Religious Attitude Student IKIP Siliwangi Approaching successfully